2005
DOI: 10.1073/pnas.0409523102
|View full text |Cite
|
Sign up to set email alerts
|

Strategic interactions in multi-institutional epidemics of antibiotic resistance

Abstract: The increasing frequency of antibiotic resistance in hospital-acquired infections is a major public health concern that has both biological and economic causes. Here we develop conceptual mathematical models that couple the economic incentives and population biology of hospital infection control (HIC). We show that the optimal investment by a hospital for HIC changes with the proportion of patients already colonized with antibiotic-resistant bacteria (ARB) at the time of admission. As that proportion increases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
74
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(80 citation statements)
references
References 31 publications
2
74
0
3
Order By: Relevance
“…Patient movements have also been suggested as an important factor in the spread of antimicrobial resistance between healthcare institutions (18,19). Mathematical models have confirmed the importance of patient movements in the propagation of nosocomial pathogens (20)(21)(22)(23)(24)(25).…”
mentioning
confidence: 85%
“…Patient movements have also been suggested as an important factor in the spread of antimicrobial resistance between healthcare institutions (18,19). Mathematical models have confirmed the importance of patient movements in the propagation of nosocomial pathogens (20)(21)(22)(23)(24)(25).…”
mentioning
confidence: 85%
“…It is likely that the 'mixing' of patients and staff will have important impacts on the transmission dynamics, especially when considering multiple health-care facilities with a single community reservoir. Movements of individuals (particularly persistent carriers) between hospitals, long-term care facilities and community populations need to be included in order to model MRSA transmission dynamics effectively [31,32].…”
Section: Limitations Of the Modelmentioning
confidence: 99%
“…Because MRSA can be carried asymptomatically for a long time (14), readmission could introduce a previously acquired strain into a new hospital (15). Thus, failure of one hospital's infection control could in principle affect the prevalence of MRSA in other hospitals that share patients with it (16). Previous studies have suggested that patient transfer or patient referral patterns (17) could affect the prevalence of MRSA in hospitals (1, 2, 16, 18, 19), on the basis of theoretical arguments and observations that clones of MRSA appear in neighboring hospitals.…”
mentioning
confidence: 99%